405 Physiotherapy telehealth to reduce falls in aged care (TOP UP): trial protocol. (20th November 2022) - Dawson, Rik; Sherrington, Cathie; Oliveira, Juliana; Pinheiro, Marina
Abstract : Background: Tailored balance and strengthening exercise programs delivered by physiotherapists have been shown to improve mobility and prevent falls in older people. Telehealth physiotherapy is emerging as an innovative method of service delivery for older people during the COVID-19 pandemic. This trial aims to establish the effect on mobility and falls of a telehealth physiotherapy program compared to usual care in older people aged 65+ years receiving aged care services. Methods: This hybrid Level 1 effectiveness and implementation randomised controlled trial aims to recruit 240 older people receiving aged care services aged 65+ years. Participants will be randomised to either: (1) the Telehealth Physiotherapy (TOP UP) Program or (2) a waitlist control group. The primary outcome is the change in mobility as measured by the change in the Short Performance Physical Battery (SPPB) test score from baseline to 6 months after randomisation. Secondary outcomes include rates of falls, 5 times sit-to-stand, quality of life, and goal attainment. A process evaluation that includes an economic analysis, acceptability, and other qualitative measures will be conducted. Trial registration: ACTRN 12621000734864. Results: Three aged care partners (2 metro and one rural) have signed the clinical trial agreement with the first participant randomised in September 2021. To date, we have randomised 26 participants in RACF and 25 participants in home care. Learning Outcomes: Increasing the understanding of the effectiveness, cost-effectiveness, and implementation strategies is required to support telehealth physiotherapy uptake and sustainability for mobility and fall prevention programs in aged care.